Pengembangan Media Pembelajaran Matematika Integrasi Keislaman Berbasis Digital untuk Mendukung Implementasi Kurikulum Merdeka dan Profil Pelajar Pancasila - Khotimah, Nur; Mukmin, Muhammad Islahul (Jurnal Tadris Matematika, 2024)
The lack of mathematics learning media used and the lack of students' understanding of the sequence and series material often result in students having difficulty solving problems in the material. In mathematics learning, students not only obtain cognitive values, but also affective values ​​that can support the implementation of the Independent Curriculum and the Pancasila Student Profile, one of which is the first dimension. This study aims to develop digital-based Islamic-integrated mathematics learning media that can make it easier for students to understand the material, namely in the form of learning videos developed using Powtoon on the sequence and series material for class X. This study is a Research and Development (RnD) study with the ADDIE development model consisting of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data collection instruments in this study were in the form of field note sheets, validation sheets, and questionnaire sheets. The Islamic-integrated mathematics learning video obtained validation results from media experts of 85.71%, material experts of 85.42%, integration experts of 78.125%, and language experts of 85.71%. In addition, the percentage of practicality from teachers was 92%, from small group trials it was 83.75%, and from large group trials it was 78.63%. Based on the questionnaire given, students became more knowledgeable about sequences and series.